PENYELESAIAN MASALAH DAN PENGAMBILAN KEPUTUSAN - Salsa Miftahul Jannah; Tasya Ramadhan; Aulia Putri; Muhammad Hasan Basari (JIP: Jurnal Ilmu Pendidikan, 2025)
Problem solving and decision-making are two interrelated cognitive skills that play a crucial role in various contexts, both individual and organizational. The problem-solving process involves identifying issues, analyzing causes, formulating alternative solutions, and evaluating outcomes. Meanwhile, decision-making focuses on selecting the best course of action from available options based on rational criteria and situational considerations. Research on these two concepts shows that a systematic approach, the use of accurate data, and critical thinking skills can improve decision effectiveness. Furthermore, psychological factors such as intuition, cognitive biases, and experience also influence the quality of decisions. By understanding the relationship between problem solving and decision-making, individuals and organizations can optimize strategies to address challenges and achieve goals more efficiently